CRIMINALITY AND POVERTY IN SUMATRA - nairobi nairobi; Ambya Ambya; Alin Hafiza Amanda; Fadeli Yusuf Afif (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study analyzes the effect of crime on poverty in Sumatra, in addition to using the Human Development Index variable and also the open unemployment rate as independent variables. Fixed Effect Model is the best method used in this study, panel data consisting of 9 years and 10 provinces in Sumatra. Increasing security and comfort is an important thing that must be accommodated in the form of a law. This is a certainty as well as a guarantor to prevent criminal acts by taking action in the form of strict punishment from the government